Formation of Shear Zone's Defect Structure in F. C. C. Metals; Advanced Materials Research : Radiation and nuclear techniques in material science; Vol. 1084 : Physical-Technical Problems of Nuclear Science, Energy Generation, and Power Industry (PTPAI -2014) - Starenchenko V. A. Vladimir Aleksandrovich; Cherepanov D. N. Dmitry Nikolaevich; Selivanikova O. V. Olga Valerievna; Barbakova E. A. (Materials Science and Technologies, 2015)
Title screen